Development of Protocols for Regeneration and Transformation of Apomitic and Sexual Forms of Dallisgrass (Paspalum dilatatum Poir.) - Schrauf, Gustavo E.; Voda, Lisandro; Zelada, Alicia M.; García, Ana María; Giordano, Andrea; Roa, Pablo Peralta; Guitian, Juan; Rebori, Juan; Ghio, Sergio; Couso, Luciana; Castro, Lautaro; Musacchio, Eduardo; et al. (Frontiers in Plant Science, 2022)
Paspalum dilatatum (common name dallisgrass), a productive C4 grass native to South America, is an important pasture grass found throughout the temperate warm regions of the world. It is characterized by its tolerance to frost and water stress and a higher forage quality than other C4 forage grasses. P. dilatatum includes tetraploid (2n=40) sexual and pentaploid (2n=50) apomictic forms, but is predominantly cultivated in an apomictic monoculture, which implies a high risk that biotic and abiotic stresses could seriously affect grass productivity. The obtention of reproducible and efficient protocols of regeneration and transformation are valuable tools to obtain genetic modified grasses with improved agronomics traits. In this review, we present the current regeneration and transformation methods of both apomictic and sexual cultivars of P. dilatatum, discusses their strenghts and limitations, and focuses on the perspectives of genetic modification for producing new generation of forages. The advances in this area of research leads us to consider Paspalum dilatatum as a model species for the molecular improvement of C4 perennial forage species.